The short-chain fatty acids as potential protective agents against Callosobruchus maculatus infestation. (March 2020) - Krzyżowski, Michał; Francikowski, Jacek; Baran, Bartosz; Babczyńska, Agnieszka
Abstract: The cowpea weevil, Callosobruchus maculatus, is one of the most common pests of stored legumes. Its occurrence adversely affects the quality of stored beans, making them unfit for consumption, resulting in substantial financial losses. The aim of this study was to investigate the potential insecticidal properties of the volatile fatty acids (VFAs) (C1 – C5) and their influence on the insect's physiology and behavior. All VFAs in concentrations equal to 4  μl and 8  μl showed fumigant toxicity significantly higher from the control. The strongest effect was observed in the case of propionic and valeric acid in volume of 4  μl and 8  μl, where mortality was close to 100%. Except for butyric acid, all acids showed a significant repellent effect. Additionally, all VFAs significantly decreased the number of infested beans and influenced the locomotor activity. Of all tested acids only the formic acid did not affect the oxygen consumption of the insects. As the studied VFAs have noteworthy properties against C. maculatus, they could be considered as promising agents in new strategies for stored products pest management. Graphical abstract: Image 1 Highlights: The influence of five VFAs was assessed (namely, formic, acetic, propionic, butyric and valeric acid). Presented manuscript is the first report on the influence of the VFAs on C. maculatus . The strongest effects were observed in groups treated with propionic acid. All tested acids significantly reduced the number of eggs laid on the surface of the beans.